Relación neutrófilos-linfocitos como predictor de riesgo de recurrencia de cáncer de tiroides - Paz-Ibarra, José Luis (2025)
Introduction. The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory biomarker associated with poor prognosis and recurrence in differentiated thyroid cancer (DTC). Its usefulness as a complementary tool to the American Thyroid Association (ATA) risk stratification still requires clinical validation. Objective. To assess the discriminatory ability of the neutrophil-to-lymphocyte ratio as a predictor of thyroid cancer recurrence risk. Methods. A cross-sectional, analytical, observational study conducted at the Edgardo Rebagliati Martins National Hospital EsSalud between June 2023 and June 2024. Patients diagnosed with DTC who had undergone total thyroidectomy and had available preoperative blood counts were included; those with inflammatory or infectious processes, additional neoplasia, or use of immunosuppressants were excluded. According to ATA 2015, patients were classified as low, intermediate, and high risk of recurrence. Discriminatory capacity and optimal cutoff points were evaluated using ROC curves. Results. 104 patients were analyzed, with a mean age of 51,9 ± 13,5 years, with a female predominance (87,5%). The 41,4% were classified as having low risk of recurrence, 53,9% as intermediate, and 4,8% as high. The AUC for differentiating high vs. low-intermediate risk was 0,69 (95% CI: 0,43–0,95), and for intermediate-high vs. low risk it was 0,58 (95% CI: 0,47–0,69). Conclusion. The NLR did not show discriminatory ability to differentiate the levels of recurrence risk in thyroid cancer according to the ATA classification.